AN UNPUBLISHED LETTER OF SAMSU-ILUNA KING OF BABYLON. (December 2021) - Khwshnaw, Ardalan; Mohammed, Khana
Abstract : This short letter of Samsu-iluna (1749–1712 B.C), king of Babylon, is preserved in the Slemani Museum, along with a number of other Old Babylonian documents. The article gives a brief overview of the letters of Samsu-iluna. The short letter appears to be addressed to one Ipqu-Gula, who may be a šassukkum -official (the head of the cadastre-office) from Isin. The article presents a copy, transliteration, translation of and commentary on this cuneiform document, which adds to the small number of letters sent directly by Samsu-iluna that are currently available.